Penerapan Media Pop Up Book untuk Meningkatkan Kreativitas Siswa Sekolah Dasar Nurul Khoir Kota Jambi - Noni Indrianti; Vioni Saputri (Lembag, 2025)
This research is based on the fact that during the IPAS learning process, many students are still unable to express their opinions, and students are shy to ask about things they don't understand. The purpose of this study is to describe the use of pop-up book media to enhance creativity, describe the obstacles in implementing human respiratory system learning using pop-up book media and how to overcome them in VB class students of Nurul Khoir Elementary School, Jambi City. This research uses a classroom action research design. This research consists of two cycles, each cycle consists of four stages, namely planning, implementation, observation and reflection. The data collection techniques in this study were observation, interviews, and documentation. The subjects of this study were VB class students of Nurul Khoir Elementary School, Jambi City. The results of the data analysis showed that using pop-up book media can enhance student creativity in IPAS learning on the human respiratory system material for VB class students of Nurul Khoir Elementary School, Jambi City. The details of the results of student creativity using pop-up book media have increased from cycle I to cycle II with an average value of 71.56% with a sufficient category and increased to 84.93% with a good category. It is concluded that using pop-up book media can enhance student creativity in IPAS learning on the human respiratory system material for VB class students of Nurul Khoir Elementary School, Jambi City.